Factors affecting conception rate in AI bred cattle under field conditions of Bihar - BANSAL, K; BHAGAT, R L; SINHA, A K; YADAV, A L; PHADKE, N L (The Indian Journal of Animal Sciences, 2019)
Data on 1,28,075 artificial inseminations (AI) performed during 6 years (January 2010 to November 2015) on 1,02,386 field animals owned by 55,685 farmers’ from 69 cattle development centres spread across four districts of Bihar were collected and analyzed. Whole data set was classified according to districts (Chhapra, Samastipur, Siwan, Vaishali), economic status of farmers (APL, BPL), animal breed (HF cross, Indigenous, Jersey cross, Nondescript), lactation order/parity of animal (heifer, first, second, third, fourth, fifth, sixth and above), animal body condition score (all ribs exposed, no rib exposed, one rib exposed, two ribs exposed, three ribs exposed), heat stage (early, mid, late), season of AI (rainy-June to September, winter-October to January, summer-February to May) and sire used for AI (Gir, HF purebreed, HF crossbreed, Jersey purebred, Jersey crossbreed, Sahiwal). Logistic regression analysis was used to compute the odds ratio and probability of conception rate. The results revealed that overall mean conception rate as 52.16% and it was noticed significantly higher in Chhapra district, BPL group of farmers, Jersey crossbreed animals, animals having third lactation, animals exhibiting three ribs exposed, mid heat and animals inseminated with HF purebred semen compared with respective groups of parameters under study. However, effect of season of AI did not affect conception rate in rural animals under field conditions of Bihar. ACKNOWLEDGEMENT Authors are very much grateful to the President, BAIF for his encouragement. Financial support from Department of Animal Husbandry, Government of Bihar and help rendered by Godhan project team for data compilation is gratefully acknowledged